Electronic structure, chemical bonding, and geometry of pure and Sr-doped CaCO3 - Stashans, A. (2007)
The electronic structure, chemical bonding, geometry, and effects produced by Sr-doping in CaCO3 have been studied on the basis of density-functional theory using the VASP simulation package and molecular-orbital theory utilizing the CLUSTERD computer code. Two calcium carbonate structures which occur naturally in anhydrous crystalline forms, calcite and aragonite, were considered in the present investigation. The obtained diagrams of density of states show similar patterns for both materials. The spatial structures are computed and analyzed in comparison to the available experimental data. The electronic properties and atomic displacements because of the trace element Sr-incorporation are discussed in a comparative manner for the two crystalline structures. © 2007 Wiley Periodicals, Inc.